Sistem Pemantauan Pertumbuhan Anggrek Berdasarkan Pengolahan Citra Digital - Magnolia Gina Ro'fataka Satriorini; Raden Sumiharto; Roghib Muhammad Hujja (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2022)
Growth monitoring and plant protectionis the major aspect of horticulture because its productivity depends on the health of the plants. Manual direct measurement methods tend to be destructive  towards  observed  plants. In  this  research,  a  smart  non-contact  growth  monitoring system was implemented on a chamber with orchid plants asthe objectsobserved. The images of  the  orchids  were  taken  and  became  the  input  of  the  system  to  be  processed  to  estimate  the height of the plants.The contour of the orchid plant as the object was obtained and the height was calculated based on the highest and the lowest contour.The result shows that the developed system is proven to be capable of measuring orchid’s height in real-time  with  accuracy  more than  95,7%.  Thus,  this  system will  effectively  help  farmers  to improve  the  quality  and  the quantity of the plant’s productivity.